Hubungan Kecerdasan Emosional dengan Kecanduan Game Online di Kalangan Dewasa Awal - Ayuni, Sarah; Desco, Puja Putria; Jannah, Miftahul; Putra, Aditya Andhika; Mahbubulhaq, Ibnu Zafad; Salsabilla, Ghina Syira (Causalita, 2026)
This research aims to identify the relationship between emotional intelligence and online game addiction among young adults. The research method used is quantitative with a correlational approach. The research process includes stages of data collection using instruments in the form of emotional intelligence and online game addiction questionnaires, data processing through statistical analysis, and interpretation of the results. Based on data analysis, a correlation coefficient of -0.465 was obtained with a significance level (p) = 0.000 (p<0.01). These results indicate a significant negative relationship between emotional intelligence and online game addiction, where individuals with higher emotional intelligence tend to have lower levels of online game addiction. This research contributes to the understanding of psychological factors that influence online gaming addictive behavior, as well as its implications for interventions in young adult groups.